Application of Health Belief Model on Preventive Behaviors of Patients with Low Back Pain - Septi Ayu Arum Yuspita Sari; Dono Indarto; Mahendra Wijaya (Journal of Health Promotion and Behavior, 2018)
Background: Low back pain (LBP) has different negative impacts in some people around the world. There are many risk factors of LBP, either biology, psychology, or social economics. A psychological theory (Health Belief Model/HBM) can be applied for preventive behaviors of some human diseases. This study aimed to analyze the application of HBM on preventive behaviors of patients with LBP.Subjects and Method: This was a case-control study conducted at the medical rehabilitation policlinic, Dr. Moewardi Hospital, Surakarta, from October to November 2018. A sample of 50 LBP patients and 100 non-LBP patients was selected by fixed exposure sampling. The dependent variable was preventive behaviors. The independent variables were perceived severity, susceptibility, benefit, barrier, threat, cues to action, and self-efficacy. Data on LBP was obtained from medical record. The other data were collected by questionnaire and analyzed by path analysis.Results: LBP preventive behaviors were directly and positively associated with perceived threat (b= 0.46; 95% CI= 0.24 to 0.68; p<0.001), perceived benefit (b= 0.29; 95% CI= 0.18 to 0.40; p<0.001), and self-efficacy (b= 0.16; 95% CI= 0.08 to 0.23; p<0.001). It was indirectly associated with perceived susceptibility, perceived severity, perceived barrier, and cues to action.Conclusion: LBP preventive behaviors are directly and positively associated with perceived threat, perceived benefit, and self-efficacy. It is indirectly associated with perceived susceptibility, perceived severity, perceived barrier, and cues to action. This study supports the application of HBM to explain LBP preventive behaviors.Keywords: low back pain, Health Belief Model, path analysisCorrespondence: Septi Ayu Arum Yuspita Sari. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email:yuspitasari020993@gmail.com. Mobile: +6282338986991.Journal of Health Promotion and Behavior (2018), 3(3): 192-198https://doi.org/10.26911/thejhpb.2018.03.03.06